The Effectiveness Of Photographs To Teach Writing Descriptive Text - Lahita, Nanda (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
The study's objective is to find out whether there is a significant difference between writing descriptive text that was taught using photographs and that without using pictures. This research is experimental. This research was conducted at Sunan Drajat female Islamic boarding school, where the subjects were the 7th-grade students of the junior high school, especially in Al Aisyah Dormitory. The number of subjects in the experimental group was 35, and the subjects in the control group was 37. To collect the data, the researcher constructed a test in the form of a writing test. The data were analyzed by utilizing descriptive and inferential analysis. The research findings indicated that the mean score of the experimental group (using photographs) is 22.11 and that of the control group (without using photographs) is 21.18. The value of t-observed (3.03) is higher than the value of t-table (1.99). It means that the hypothesis is accepted (3.03 > 1.99). It can be said that there is a significant difference between writing a descriptive test for 7th-grade students who were taught using photographs and those taught without using photographs. Therefore, photographs are more effective in teaching writing descriptive text for 7th-grade students of Al Aisyah Dormitory in Sunan Drajat Female Islamic Boarding School in the academic year of 2024/ 2025.